2006
DOI: 10.2135/cropsci2006.01.0026
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Screening Method for Drought Tolerance in Cotton Seedlings

Abstract: The key to an efficient screening method is the ability to screen large amounts of plant material in the shortest time possible. Due to the complexity of drought tolerance, a quick and effective screen for this trait has yet to be established. The research reported herein was designed to evaluate a screening method for drought tolerance in cotton (Gossypium hirsutum L.) seedlings. Twenty-one converted race stocks (CRS) and two cultivars were evaluated for seedling drought tolerance (SDT) on an individual plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
(27 reference statements)
0
26
0
1
Order By: Relevance
“…The phenotypic evaluation is an important resource in the hands of breeders because of their high throughput and cost economical nature. It has been identified earlier that seedling stage is the most sensitive stage of plant growth, and thus Where ±SD= Standard deviation, RL=Root length, SL=shoot length, RWC=Relative water content, ELWL=Excise Leaf Water Loss, SSI=Stress susceptibility index N=Normal water supply and D= Water deficit condition screening for stress tolerance at this stage has been targeted in various crops like wheat (Gesimba et al, 2004;Farshadfar et al, 2012), sorghum (Ali et al, 2011;Bibi et al, 2012) and cotton (Cook, 1989;Longenberger et al, 2006;Ahmad et al, 2009;Iqbal et al, 2011). Present studies were also based on the model used by these researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypic evaluation is an important resource in the hands of breeders because of their high throughput and cost economical nature. It has been identified earlier that seedling stage is the most sensitive stage of plant growth, and thus Where ±SD= Standard deviation, RL=Root length, SL=shoot length, RWC=Relative water content, ELWL=Excise Leaf Water Loss, SSI=Stress susceptibility index N=Normal water supply and D= Water deficit condition screening for stress tolerance at this stage has been targeted in various crops like wheat (Gesimba et al, 2004;Farshadfar et al, 2012), sorghum (Ali et al, 2011;Bibi et al, 2012) and cotton (Cook, 1989;Longenberger et al, 2006;Ahmad et al, 2009;Iqbal et al, 2011). Present studies were also based on the model used by these researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Selection for morpho-physiological components of drought, at the seedling stage, is of great importance because tolerance, at this critical growth stage, contributes to high yield of seed cotton (Longenberger et al, 2006;Iqbal et al, 2010). It is particularly true when the breeding program is targeting the water stress tolerance (Khan et al, 2008;Jajarmi, 2009;Qayyum et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The relatively more drought-resistant cultivars had the greatest values for all the four variables. A seedling drought-tolerance protocol was developed as a new method to select drought-tolerant individuals from various genotypes subjected to sequential drought cycles (Longenberger et al, 2006). Iqbal et al (2010) have studied shoot and root traits under normal water and water stress conditions, and they concluded that the existence of variability in cotton germplasm suggests that genetic improvement can be achieved through selection and breeding provided that the variability is affected by genetic components.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, selection criteria should be easy, rapid and capable of evaluating plant performance at a critical developmental stage in both small and large populations. Selection of suitable Abbreviations: LRD, lateral root density; NLR, lateral root number; R%, recovery percent; RL, root length; R:S, root-to-shoot ratio; RW, root weight; SL, shoot length; SW, shoot weight; W 1 , optimum moisture level; W 2 , lowmoisture level; WRI, wilting rate index genotypes on the basis of seedling traits has been considered a reliable technique for evaluating a large number of genotypes for drought tolerance (Tomar and Kumar 2004;Basal et al 2005;Longenberger et al 2006).…”
mentioning
confidence: 99%